Expression of unique gene signature distinguishes TCRαβ+/BCR+ dual expressers from CD3+CD14+ doublets. Issue 4 (9th February 2022) - Jie, Chunfa; Ahmed, Rizwan; Hamad, Abdel Rahim A.
Abstract: Increasing evidence shows pathophysiological significance of rare immune cells, necessitating the need for reliable and proper methods for their detection and analysis. We have recently identified a new lymphocyte that coexpresses lineage markers of T‐ and B‐cells including T cell receptor and B cell receptor (called dual expressers, DEs). Because of the peculiar phenotype of DEs, we used multiple techniques to authenticate their identity (fluorescence‐activated cell sorting [FACS], scRNAseq, EBV cell lines, and imaging flow cytometry). In an recent article published in this journal, Burel and colleagues successfully detected DEs using FACS and imaging microscopy. Yet they claimed, based on the profile of what they called naturally occurring CD3 + CD14 + T cell/monocyte complexes that the scRNAseq signature of DEs resembles that of cell–cell complexes. Serious flaws in their analysis, however, invalidate their conclusions. Unlike the CD3 + CD14 + complexes, DEs have a distinct identity due to expression of a unique set of signature genes. Without a clear explanation, Burel and colleagues excluded these genes from their analysis, thereby effectively stripped DEs from their identity. Inclusion of these genes as described in this communication restores the identity of DEs. Moreover, contrary to the claim of Burel and colleagues, B‐ and T‐cell specific genes are similarly expressed in DE cells. Abstract :